Utility of fine-needle aspiration cytology as a screening tool in diagnosis of breast lumps - Gupta, Rajat; Dewan, Deepika; Kumar, Dinesh; Sharma, Rameshwar (International Surgery Journal, 2017)
Background: Fine-needle aspiration cytology (FNAC) has proved to be a rapid, safe, cost effective and good screening or initial diagnostic tool for early diagnosis and management of palpable breast swellings. The present study was conducted to describe and categorize various breast lesions on FNAC. The study also aimed to find out the diagnostic accuracy of FNAC procedure. Methods: This study was carried out on 175 patients who presented with palpable breast swellings in Government Hospital Gandhi Nagar, Jammu, Jammu and Kashmir, India and subsequently referred to Pathology Department of Govt. Hospital Gandhi Nagar over a period of two years and eight months from January 2013 to September 2015. Lesions were categorized as per cytomorphological features obtained on FNAC. Histopathological correlation was done on 68 cases inclusive of all malignant cases. Results: 156 (89%) cases were categorized as benign and 19 cases (11%) as malignant on FNAC out of 175 cases. The most common benign lesion was fibro adenoma (41%) and the most common breast carcinoma was ductal carcinoma (65%). Sensitivity, specificity, positive predictive value, negative predictive value, LR+ and LR- came out to be 85%, 95.8%, 89%, 93.8%, 20.4 and 0.15 respectively. Conclusions: FNAC is a good screening procedure for initial diagnosis of breast lumps. It is highly useful procedure in secondary care centres due to its cost effectiveness, rapid and safe nature.